2022
DOI: 10.1016/j.beth.2021.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Improving Mental Health on College Campuses: Perspectives of Indian College Students

Abstract: Improving mental health on college campuses: Perspectives of Indian college students. Behavior Therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…However, the educated younger generation having access to lot of information on the internet may have contributed to their overall better awareness on this topic (Pretorius et al, 2019). The findings also highlight the need to create more awareness among youth to encourage help-seeking behavior, which has been underscored in previous literature about campaigns being done to minimize the stigma around it (Gaiha et al, 2021;Wasil et al, 2022).…”
Section: Discussionmentioning
confidence: 80%
“…However, the educated younger generation having access to lot of information on the internet may have contributed to their overall better awareness on this topic (Pretorius et al, 2019). The findings also highlight the need to create more awareness among youth to encourage help-seeking behavior, which has been underscored in previous literature about campaigns being done to minimize the stigma around it (Gaiha et al, 2021;Wasil et al, 2022).…”
Section: Discussionmentioning
confidence: 80%
“…Academic and social stressors contribute to mental health. 44 - 46 In this study, 62% of the students were working, and some were working in the hospital, where they were often shorthanded. Our results reflected collective intellectual, physical, and emotional fatigue.…”
Section: Discussionmentioning
confidence: 80%
“…49 Participants responded that they need time to manage physical health and strategies for self-care, such as breaks, PA, and sleep hygiene. 44,46 Our findings revealed that students want to learn more about stress alleviating strategies and MBPA intervention to support personal growth.…”
Section: Perceived Stress During Covid-19mentioning
confidence: 83%
“…This reinforces the importance of mental health initiatives in educational institutions. Wasil et al (2022) in their study illustrated, through 3 questions, how open-ended surveys can be a useful and feasible way to gather input from students in low-and middle-income countries. The present study incorporated a similar strategy of asking 4 open-ended questions related to happiness.…”
Section: Discussionmentioning
confidence: 99%